Charge Transport and Conductance Switching of Redox‐Active Azulene Derivatives. Issue 39 (24th August 2016) - Schwarz, Florian; Koch, Michael; Kastlunger, Georg; Berke, Heinz; Stadler, Robert; Venkatesan, Koushik; Lörtscher, Emanuel
Abstract: Azulene (Az) is a non‐alternating, aromatic hydrocarbon composed of a five‐membered, electron‐rich and a seven‐membered, electron‐poor ring; an electron distribution that provides intrinsic redox activity. By varying the attachment points of the two electrode‐bridging substituents to the Az center, the influence of the redox functionality on charge transport is evaluated. The conductance of the 1, 3 Az derivative is at least one order of magnitude lower than those of the 2, 6 Az and 4, 7 Az derivatives, in agreement with density functional theory (DFT) calculations. In addition, only 1, 3 Az exhibits pronounced nonlinear current–voltage characteristics with hysteresis, indicating a bias‐dependent conductance switching. DFT identifies the LUMO to be nearest to the Fermi energy of the electrodes, but to be an active transport channel only in the case of the 2, 6 and the 4, 7 Az derivatives, whereas the 1, 3 Az derivative uses the HOMO at low and the LUMO+1 at high bias. In return, the localized, weakly coupled LUMO of 1, 3 Az creates a slow electron‐hopping channel responsible for the voltage‐induced switching due to the occupation of a single molecular orbital (MO). Abstract : By varying the attachment points to the azulene center, the influence of the redox functionality on charge transport is evaluated. Among the three substituent patterns, only the 1, 3 Az derivative displayed nonlinear and hysteretic transport behavior. Its weakly coupled LUMO is identified by DFT to be chargeable, leading to a transport mechanism also involving a slow electron‐hopping channel, which is responsible for the switching due to single MO occupation.